Outdoor recreation and the private forest owner: Place attachment, social values, and public access - Johnsson, Frida; Beery, Thomas (Frontiers in Conservation Science, 2023)
The Swedish National Forest Program emphasizes that the forest can be more multifunctional where the values created by human experiences of the forest, i.e., social values, can be used for tourism and outdoor recreation, leading to rural development and sustainable growth. To develop multifunctional forests in this respect, private forest owners' perspectives on development are critically important. For example, the place attachment of the private forest owners affects how private forest owners manage their forests. Therefore, it is crucial to consider private forest owners' perspectives when planning landscapes. The study area is a region in southwest Sweden (Hallandsås) designated as a national interest area for outdoor recreation. There exists an interest in expanding and developing trail systems and nature tourism based on the perception of the areas as having great outdoor recreation value. This article aims to present findings from a study that investigated the potential for outdoor recreation development in the forests of Hallandsås. A questionnaire was sent out to private forest owners, which contained questions about social values, perspectives on the Swedish right of public access, development of outdoor recreation, and place attachment. The results showed that private forest owners considered health, well-being, and a good living environment the most important social values of their forested lands. The identity and cultural heritage value of private forest lands and the value of working on the land were the second and third most highly identified forest social values. Outdoor recreation was not identified as a top forest social value. The analysis identified seven key factors that must be considered with outdoor recreation development, given concerns and the importance of other forest social values.